Steel Pipe Internal Corrosion Protection Using Magnesium Anode: Impact of Protective Potential and Phase Layer Formation on Corrosion Rate - Georgii Vasyliev; Yuriy Gerasymenko (Advances in Materials Science and Engineering)
The influence of magnesium anode dissolution in pipe filled with potable water on the steel corrosion rate was investigated. Steel corrosion rate was measured using the weight loss technique, and linear polarization resistance measurements were used to estimate the formation kinetics and protective abilities of the phase layer on the metal surface. The cathodic current distribution along steel pipe was measured using a microammeter and compared with the computer model. The results clearly demonstrate that the reduction of metal corrosion rate is at least 2.8 times in the region where cathodic protection distributes inside the pipe. However, for the remaining part of the metal pipe, the reduction of corrosion rate of 1.5 times was obtained due to the formation of the phase layer on the metal surface that leads to the reduction of oxygen supply. The results obtained in the study can be further applied for designing and maintenance of water supply systems.